Migration, spillovers, and trade diversion: The impact of internationalization on domestic stock market activity - Levine, Ross; Schmukler, Sergio L. (Journal of Banking & Finance, 2007)
This paper studies the relation between internationalization (firms cross-listing, issuing depositary receipts, or raising capital in international stock markets) and the trading activity of the remaining firms in domestic markets. Using a panel of 3000 firms from 55 emerging economies during 1989–2000, we find that internationalization is negatively related to the trading activity of domestic firms. We identify two channels. First, the trading of international firms migrates from domestic to international markets and this migration along with the reduction in domestic trading of international firms has negative spillover effects on domestic firm trading activity. Second, there is trade diversion within domestic markets as trading activity shifts out of domestic firms and into international firms.